2015
DOI: 10.1080/19425120.2015.1074966
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stock Structure of Terapon jarbua in Taiwanese Waters

Abstract: Over the past century, stock identification, which is crucial for fisheries stock assessments, has relied heavily on intraspecies variations to differentiate management units. In recent years, however, DNA approaches have shed additional light on some aspects of the natural history and ecology of species and stocks. The Crescent Grunter Terapon jarbua is widely distributed across the Indo-Pacific region. It inhabits coastal waters with sandy substrates and tends to aggregate in estuaries. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 54 publications
(55 reference statements)
2
8
0
Order By: Relevance
“…The inference of population expansion is further supported by the star-like patterns in Figure 3. Our results agree with an earlier study of T. jarbua populations from the Taiwanese waters which exhibited similarly high population haplotype diversity ranging from 0.86 to 1.00 as inferred from COI and Cyt b sequence data (Liu et al 2015). In a study on T. jarbua populations from the Gulf of Aden, Lavergne et al (2014) reported similarly high genetic diversities ranging from 0.216 to 0.698.…”
Section: Genetic Diversitysupporting
confidence: 92%
See 4 more Smart Citations
“…The inference of population expansion is further supported by the star-like patterns in Figure 3. Our results agree with an earlier study of T. jarbua populations from the Taiwanese waters which exhibited similarly high population haplotype diversity ranging from 0.86 to 1.00 as inferred from COI and Cyt b sequence data (Liu et al 2015). In a study on T. jarbua populations from the Gulf of Aden, Lavergne et al (2014) reported similarly high genetic diversities ranging from 0.216 to 0.698.…”
Section: Genetic Diversitysupporting
confidence: 92%
“…Polymerase Chain Reaction (PCR) amplification of approximately 1000 bp from the 5'end of the Cyt b gene was performed using the primer pairs Glu31 and Thr33 (Liu et al 2015) and internal primers: Glu231 (5'-CTT ACA GGC CTC TTT CTG GCC AT-3') and Thr233 (5'-TTT GAG CTA CTA ATG CAG TAT-3') were designed for this study.…”
Section: Dna Extraction Pcr Amplification and Dna Sequencingmentioning
confidence: 99%
See 3 more Smart Citations